Preliminary Studies for One-Step Fabrication of Metallic Iron-Based Coatings on Magnesium as Temporary Protection in Biodegradable Medical Application - Yang, Yuyun; Shi, Zizhong; Cui, Xiufang; Liu, Yuejun; Jin, Guo; Virtanen, Sannakaisa; Boccaccini, Aldo R.; She, Peng (Frontiers in Materials, 2021)
Iron and magnesium are being considered as promising candidates for biodegradable materials in medical applications, both materials having their specific advantages and challenges. A hybrid of metallic iron and magnesium in a layered composite is studied in the present work, to combine the merits of both metals. A single-step dip-coating method was employed to prepare the layered composite material. Morphology, composition, crystal structure, and corrosion behavior of the Mg/Fe sheet were assessed by SEM, EDX, XRD, and electrochemical measurements. The Mg/Fe layered composite sheet is composed of the magnesium substrate, a 1-2 µm metallic iron coating, and a pompon-like Mg(OH)2/MgO top layer. Long-term open-circuit potential measurements revealed that the Mg/Fe sheet samples exhibit a “self-healing” effect in Dulbecco’s modified Eagle’s medium.